2021
DOI: 10.1101/2021.06.02.21258076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic characterization and Epidemiology of an emerging SARS-CoV-2 variant in Delhi, India

Abstract: In April 2021, after successfully enduring three waves of the SARS-CoV2 pandemic in 2020, and having reached population seropositivity of about 50%, Delhi, the national capital of India was overwhelmed by the fourth wave. Here, we trace viral, host, and social factors contributing to the scale and exponent of the fourth wave, when compared to preceding waves, in an epidemiological context. Genomic surveillance data from Delhi and surrounding states shows an early phase of the upsurge driven by the entry of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 38 publications
3
61
1
Order By: Relevance
“…[26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi. It could be shown that B.1.617.2 exhibits a very high transmissibility, as much as 50% greater than B.1.1.7, while no increase in the case-fatality ratio (CFR) was observed.…”
Section: Resultsmentioning
confidence: 96%
“…[26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi. It could be shown that B.1.617.2 exhibits a very high transmissibility, as much as 50% greater than B.1.1.7, while no increase in the case-fatality ratio (CFR) was observed.…”
Section: Resultsmentioning
confidence: 96%
“…[14,30], epidemiological [10,13], and vaccine studies [15,16,31,32] suggests that variants with E484K, T478K, or E484Q mutations may partially evade prior immunity. Indeed, rapid resurgences followed variant emergence, for example in Manaus, Brazil (P.1) and Delhi, India (B.1.617.2), despite evidence of high levels of prior immunity in the population [11,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…S2), where a previously dominant variant (B.1 lineage) was still prevalent by December, and very few genomic sequences have been uploaded from these places in the period of study. (1). The group also showed that this variant is as much as 50 % more transmissible than B.1.1.7 and dominated in the samples (76%) analyzed from vaccine breakthrough infections in Delhi (1).…”
mentioning
confidence: 97%
“…Accumulating evidence suggests that B.1.617 lineage variants are more transmissible (5-10) and perhaps more lethal (8) than B.1.1.7 (a.k.a. alpha variant), which had been a dominant strain in Indian population before the arrival of second wave (1). The studies have shown a significant reduction in the neutralization against B.1.617 lineage variants by antibodies received from natural infections and manycurrently used COVID-19 vaccines and multiple monoclonal antibodies (5)(6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation